Physiological markers of exercise capacity and lung disease severity in cystic fibrosis. Issue 4 (24th November 2016) - Smith, Laurie; Reilly, Charles C.; MacBean, Victoria; Jolley, Caroline J.; Elston, Caroline; Moxham, John; Rafferty, Gerrard F.
ABSTRACT: Background and objective: Peak aerobic capacity (VO2 peak) is an important outcome measure in cystic fibrosis (CF), but measurement is not widely available and can be influenced by patient motivation, pain and fatigue. Alternative markers of disease severity would be helpful. Neural respiratory drive, measured using parasternal intercostal muscle electromyography (EMGpara), reflects the load to capacity balance of the respiratory system and provides a composite measure of pulmonary function impairment in CF. The aim of the study was to investigate the relationship between exercise capacity, EMGpara and established measures of pulmonary function in clinically stable adult CF patients. Methods: Twenty CF patients (12 males, median (range) age: 22.3 (17.0–43.1) years) performed the 10‐m incremental shuttle walk test (ISWT) maximally with contemporaneous measures of aerobic metabolism. EMGpara was recorded from second intercostal space at rest and normalized using peak electromyogram activity obtained during maximum respiratory manoeuvres and expressed as EMGpara%max (EMGpara expressed as a percentage of maximum). Results: VO2 peak was strongly correlated with ISWT distance (r = 0.864, P  < 0.0001). Lung gas transfer (TL CO) % predicted was best correlated with VO2 peak (r = 0.842, P  < 0.0001) and ISWT distance (r = 0.788, P  < 0.0001). EMGpara%max also correlated with VO2 peak (−0.757, P  < 0.0001), while the relationships between exercise outcome measures and forced expiratory volume in 1 s (FEV1 ) % predicted and forced vital capacity (FVC) % predicted were less strong. A TL CO% predicted of <70.5% was the strongest predictor of VO2 peak <32 mL/min/kg (area under the curve (AUC): 0.96, 100% sensitivity, 83.3% specificity). ISWT distance and EMGpara%max also performed well, with other pulmonary function variables demonstrating poorer predictive ability. Conclusion: TL CO% predicted and EMGpara%max relate strongly to exercise performance markers in CF and may provide alternative predictors of lung disease progression. Abstract : A novel marker of cystic fibrosis (CF) lung disease severity, inspiratory muscle electromyogram activity, was investigated in 20 adult CF patients. Both lung gas transfer (TL CO) % predicted and inspiratory muscle electromyogram activity related strongly to exercise performance and therefore may be useful in CF lung disease management.